The Legal Responsibility of Notaries for Their Involvement in Price Mark-Up Practices in Land Acquisition Compensation - Mohhamad Khemal Pasya; Putra Hutomo; Mulyadi Mulyadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was This study aims to analyze the legal responsibility of notaries involved in price mark-up practices in land acquisition compensation, examining both juridical and practical aspects. This research employs a normative juridical approach, using statutory and doctrinal legal materials, combined with a case study analysis of land acquisition disputes involving notarial participation. Data were collected from laws, regulations, academic literature, and legal cases, then analyzed qualitatively to identify patterns of legal liability and compliance issues. Findings indicate that notaries who participate in price mark-up practices may be held civilly and administratively liable under the Notary Law, particularly when failing to act in accordance with their duties of accuracy, transparency, and legality. Case studies demonstrate that such practices often involve misrepresentation of land values, causing financial harm to landowners and potential conflicts with government acquisition standards. The research also highlights gaps in enforcement, emphasizing the need for stronger oversight and clearer procedural guidelines. Notaries bear significant legal responsibility in land acquisition compensation, and their involvement in price mark-up practices constitutes a breach of professional and legal duties. Ensuring strict adherence to notarial obligations is essential to protect public trust, prevent exploitation, and uphold the integrity of land acquisition processes in Indonesia.